Surface Stoichiometry and Roughness of a Degraded A380 Alloy after Casting, Technical Cleaning and Packaging - Darja Steiner Petrovič (MDPI AG, 2021)
The surface stoichiometry of the degraded surface of a commercial Al–Si casting was investigated. The die-cast component was previously stored in a sealed plastic envelope. After that, surface stains in the form of white layers were observed. X-ray photoelectron spectroscopy (XPS) was used to study these layers. For comparison, a seemingly unaffected area as well as a freshly cut surface of the casting were also analysed. In order to additionally assess the surface condition, surface roughnesses were measured. Based on the binding energies (BEs) of the Al and O in the XPS spectra, and the stoichiometric results, it was concluded that the surface layers of the degraded and undegraded samples consist mostly of aluminium oxide and aluminium hydroxide. Furthermore, sodium phosphate from the leftover detergent and silicon oxide were detected in both analysed areas. Analyses of the Al KLL Auger transition were used to corroborate this. The relative shares of Al oxide vs. hydroxide based on the elemental concentrations were determined. The chemical compositions and chemical states of the elements in the top layers were thus obtained. The combination of surface-sensitive analytical techniques was found to be a suitable tool for the ex-post identification of the source of defects.